An Empirical Analysis on Sexual Attitudes among Police Officers (International Journal of Innovative Research in Engineering & Management, 2021)
The most common crimes in the  country are rape and other sexual assaults. It is observed  that the pace is rising with time. Rape myth is a phrase  that may be interpreted in a variety of ways, but it  generally refers to a false idea about unwanted or non onsensual sexual intercourse. The majority of rape  myths promote victim guilt. This is an empirical study on  the myth of rape and sexual attitudes among male and  female police officers in Bangalore. Eleven female and  32 male police officers of various age groups and  categories make up the sample, which is made up of  distinct groupings of men and females. The of model technique was Purposive Sampling Technique, and the  respondents' responses were recorded using the Illinois  Rape Myth Acceptance (IRMA) Measure and Sexual Attitude-Scale (SAS). There was no significant difference  in Rape Myth and Attitude toward Pre-Marital Sex  between male and female police officers, according to the  findings. When compared to female police officers, men  officers were shown to have a more positive attitude of  Pre-Marital Sex. There was a significant disparity in  attitudes about pornography between male and female  cops. When compared to female police officers, male  cops were shown to have a more positive view towards  pornography.
Keywords: Attitude; Commits Rape; Male and Female; Police Officers